Hypercalcemia in Upper Urinary Tract Urothelial Carcinoma: A Case Report and Literature Review. (13th February 2013) - Asao, Keiko; McHugh, Jonathan B.; Miller, David C.; Esfandiari, Nazanene H.
Abstract : Objective . We here report a patient with upper urinary tract urothelial carcinoma with hypercalcemia likely due to elevated 1, 25-dihydroxyvitamin D. Methods . We present a clinical case and a summary of literature search. Results . A 57-year-old man, recently diagnosed with a left renal mass, for which a core biopsy showed renal cell carcinoma, was admitted for hypercalcemia of 11.0 mg/mL He also had five small right lung nodules with a negative bone scan. Both intact parathyroid hormone and parathyroid hormone-related peptide were appropriately low, and 1, 25-dihydroxyvitamin D was elevated at 118 pg/dL. The patient's calcium was normalized after hydration, and he underwent radical nephrectomy. On the postoperative day 6, a repeat 1, 25-dihydroxyvitamin D was 24 pg/mL with a calcium of 8.1 mg/dL. Pathology showed a 6 cm high-grade urothelial carcinoma with divergent differentiation. We identified a total of 27 previously reported cases with hypercalcemia and upper tract urothelial carcinoma in English. No cases have a documented elevated 1, 25-dihydroxyvitamin D level. Conclusion . This clinical course suggests that hypercalcemia in this case is from the patient's tumor, which was likely producing 1, 25-dihydroxyvitamin D. Considering the therapeutic implications, hypercalcemia in patients with upper urinary tract urothelial carcinoma should be evaluated with 1, 25-dihydroxyvitamin D.